DISTRIBUTION AND POPULATION OF PAPAYA CARMINE SPIDER MITES AND THEIR PREDATORS - Esguerra, Nelson M.; Haramoto, Frank H. (Annals of Tropical Research, 1980)
Distribution pattern and population fluctuation of the carmine spider mite and its predators were studied in unsprayed Solo papaya trees grown at the Kauai Branch Experiment Station of the University of Hawaii, at Kapaa from 1978 to 1979. In the field, the carmine spider mites were found exclusively on the undersurfaces of bottom leaves. Initially, they started to infest papaya along borders of the fields. As soon as infestation increased, mites were distributed evenly on most trees. The number of mites decreased from the proximal to the distal portions of bottom leaves. For monitoring and surveillance work, therefore, mites should be counted first on edges of a field and on mature leaves. This procedure saves time, effort and money in surveying for mites especially when the population is low and is starting to build up. In the field, the staphylinid beetle, Oligota sp.; the predatory mite, Phytoseiulus macropilis (Banks); the coccinellid beetle, Stethorus siphonulus Kapur; and 2 species of spiders, Theridion spp., preyed on the carmine spider mites. Of these predators, spider, staphylinid beetle and predatory phytoseiid mite increased with slight population buildup of the carmine spider mites. Rainfall and predators prevented outbreaks of carmine spider mites and continuously allowed the population to fluctuate at low levels.